The Impact of Urban Green Space on The Urban Heat Island Phenomenon – A Study Case in East Jakarta, Indonesia - Rizki, Amalia Rakhmawati; Tumuyu, Sri Setiawati; Rushayati, Siti Badriyah (Department of Urban and Regional Planning, Diponegoro University, 2024)
The urban heat island (UHI) phenomenon has grown disastrous in many major cities across the world, including Jakarta. The more cities worldwide that suffer this scenario, the faster global warming will occur, making it a global concern that has to be given priority. The goal of this study was to determine the distribution of UHI in each region and how land use planning may mitigate it. East Jakarta was found to have the highest UHI in Jakarta. The method of this study used spatial analysis, which consists of land surface temperature (LST) and normalized vegetation difference index (NDVI) using GIS. The analysis results showed that the area with the highest LST and the widest coverage of UHI in East Jakarta is in Cakung where the temperature has increased to 4oC, while the area with the lowest LST and the narrowest coverage of the UHI area is Cipayung. Meanwhile, Cipayung has the most urban green space and urban forest, making up roughly 5.6% and 1.96% of its area, while Matraman has the least, making up 1.09% of its area without any urban forest. Therefore, there are no areas in East Jakarta that meet the requirements of 10% urban forest and 30% green space. However, the region with the lowest UHI distribution is Cipayung, which has the greenest urban area. It shows how the presence of urban forests, affects the distribution of UHI in metropolitan areas.